An Evaluation of Staphylococci from Ocular Surface Infections Treated Empirically with Topical Besifloxacin: Antibiotic Resistance, Molecular Characteristics, and Clinical Outcomes - Schechter, Barry A. (Ophthalmol Ther, 2019)
INTRODUCTION: Understanding antibiotic resistance and toxin profiles among staphylococcal isolates in ocular infections can aid in therapeutic management and infection prevention strategies. We evaluated in vitro antibiotic resistance patterns and molecular traits of staphylococci isolated from patients with ocular surface infections. We also report on clinical outcomes for these patients following empirical treatment with topical besifloxacin ophthalmic suspension 0.6%. METHODS: This was a small observational study. Participating investigators from three clinical sites collected an initial ocular culture from the affected eye of patients presenting with ocular surface infections with presumed staphylococcal etiology. Clinical outcome data for patients with confirmed staphylococcal infections were collated later through retrospective review of patient medical records. Staphylococcal species identification in ocular cultures, in vitro antibiotic susceptibility testing, and PCR-based determination of methicillin resistance cassettes and toxin genotypes were conducted at a central laboratory. Isolates were categorized as susceptible or resistant based on systemic breakpoints, where available. RESULTS: Cultures were collected from 43 patients, and staphylococcal infections were confirmed in 25 patients. Two isolates of Staphylococcus aureus and 27 isolates of Staphylococcus epidermidis were identified. Both S. aureus isolates were methicillin-susceptible, lacked the gene encoding Panton-Valentine leukocidin, and carried few enterotoxin genes. Eight (30%) S. epidermidis were methicillin-resistant (MRSE), and 10 (37%) were ciprofloxacin-resistant. All but two MRSE isolates demonstrated multidrug resistance (MDR), and the staphylococcal cassette chromosome mec (SCCmec) type IVa was detected in five of the eight MRSE isolates. Clinical resolution of the ocular surface infection was reported in all 25 patients following treatment with besifloxacin. CONCLUSIONS: In this study, S. aureus contained few toxins, while SCCmec IVa and MDR was predominant among MRSE from ocular surface infections. Despite significant in vitro fluoroquinolone resistance, there were no cases of treatment failure with topical besifloxacin ophthalmic suspension 0.6%. FUNDING: Bausch Health US, LLC.